Strengthening palm sugar product competitiveness through digital marketing - Rela Adi Himarosa; Krisdiyanto Krisdiyanto; Azmatun Fildzah; Muhammad Baihaqi; Fajar Sofyantoro (Universitas Muhammadiyah Magelang, 2023)
Palm sugar, derived from coconuts, holds longstanding cultural significance in Indonesian society, offering substantial economic value. The hamlet of Nganti in Yogyakarta thrives on coconut farming and palm sugar production. Despite its potential, the palm sugar industry grapples with challenges such as limited market access and a lack of technological awareness. To address these issues, the application of digital marketing is envisioned to broaden market reach and establish robust branding. This community service program is designed to empower and optimize palm sugar marketing through digital strategies, targeting local palm sugar farmers and producers. Activities encompass discussions, digital marketing training, the creation of a video profile, and the establishment of digital marketing accounts. The program has successfully enhanced public understanding of digital marketing, facilitating effective product promotion. The initiation of social media accounts and profile videos serves to broaden product visibility to a wider audience. The most notable outcome is the increased accessibility to markets and heightened product sales.